A conceptual construct on value for infrastructure asset management. (April 2022) - Almeida, N.; Trindade, M.; Komljenovic, D.; Finger, M.
Abstract: Understanding the meaning of value to asset-intensive organizations and their stakeholders has been a long-standing goal of researchers and managers of the asset management community. These issues have become particularly prominent with the publication of the ISO 5500x series of standards on asset management. These standards are intended to guide asset-intensive organizations of different types towards realising value from their asset base. However, value can be defined and shaped in various ways, and a high-level conceptual construct to frame these differences is needed. Because such a construct has not yet been established, organizations have no standard guidance to systematically achieve and demonstrate that value is derived from their assets. The paper also discusses the impact of cognitive and motivational biases as well as the complexity of operational and business context while determining the meaning of value. This article presents an overview of theories on value and proposes an original high-level conceptual construct to be used by decision-makers in infrastructure organizations. This holistic proposal provides a structured understanding of the value concept and intends to assist infrastructure asset managers in establishing or developing their decision making processes at all levels of the organization. It enables decision-makers to factor in the benefits and impacts of competing decision options in organizational objectives and stakeholders' needs and expectations and promotes the grasping of opportunities and an enhanced balancing of costs, risks and performance throughout the life cycle of infrastructures. Highlights: background knowledge on the value concept. Proposed definition for value within the infrastructure asset management. High-level construct for measuring the value that is being derived from assets.